A Realistic Constraint on Authorial Creativity - Friend, Stacie (PARALAXE, 2016)
In this paper I argue that there is an important constraint on an author’s creativity when it comes to the imaginative content of stories. It may seem as if authors can create storyworlds however they choose, that there is no limit on their imaginative creativity. I claim, however, that this is not the case. I argue that readers necessarily take for granted that the background of a story is the real world; if they did not do this, they could not understand what they read. With this assumption in the background, authors can depart from reality only along some dimensions, and not all. KEYWORDS: Constraint; Creativity; Reality; Literature.